The microvascular endothelial redoxome established through tandem mass tag mass spectrometry. (14th October 2021) - Cottrill, S B; Lermant, A; Cantley, J; Murdoch, C E; Sneddon, C; ,
Abstract:  : Redox signalling plays an important role in endothelial cell (EC) physiology and pathophysiology. Proteins sense redox signals via cysteine thiol groups. A common oxidative post-translational modification (oxPTM) on cysteine thiols is S-glutathionylation which is reversed to a free thiol state by glutaredoxin (Glrx). OxPTMs alter protein function, location and stability. Identifying which proteins undergo modification will help determine the role of redox signalling in EC function. A proteome-wide screen of human cardiac microvascular endothelial cells identified redox-sensitive proteins involved in vascular signalling mechanisms. Methods: Human microvascular endothelial cells (HCMVEC, Lonza) were exposed to VEGF (50ng/ml, 24h) or hypoxia (0.5% O2, 24h) with adenoviral (ad) Glrx (Vectorlabs) overexpression or adLacZ (control). A tandem mass tag mass spectrometry system (TMT) coupled with a thiol-switch technique was used to quantify changes in redox sensitive thiol modifications. Protein lysates were treated with MMTS to alkylate unmodified thiols. Iodo-TMT six-plex probes were tagged to redox-sensitive sites after reversal of oxPTMs by DTT. Samples were pooled and processed by nLC-MS/MS. The abundance of each peptide in different conditions was compared with either adGlrx or adLacZ (control) expression to provide a ratio of changes in redox modifications. Results: Iodo-TMT analysis revealed 113 unique thiol modifications identified on 78 different proteins using a ±1.5-fold threshold in a given treatment. Additionally, 44 modifications in 33 proteins were present in at least 2 different conditions, namely Glrx under VEGF and hypoxic conditions. A STRING interaction network identified clusters of 10 proteins involved in organonitrogen synthesis and 6 proteins in angiogenesis. Jagged-1 involved in the regulation of angiogenic sprouting through the Notch pathway was established as a target of redox signalling. Identified redox sensitive cysteines were found in extracellular EFG1 and the calcium binding EGF12 domains. Seven different In Silico programs (including MutationTaster, PolyPhen-2 and PANTHER) predicting the impact of substitution mutations indicated a functional affect for these redox sensitive sites, demonstrating the importance of these residues. Conclusion: A non-biased proteomics approach identified novel thiol modifications on proteins involved in microvascular function. Future work will demonstrate the impact of these redox-sensitive thiol modifications on microvascular function to provide a better understanding of redox signalling in protein function and disease. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): MRC-DTP, European Union's Horizon 2020 research and innovation programme.